2007
DOI: 10.1177/0021998307082177
|View full text |Cite
|
Sign up to set email alerts
|

Impact Analysis of Fiber-reinforced Composites Based on Elasto-plastic Constitutive Law

Abstract: Impact analysis of 3D braided composites and laminated plane woven fabric composites was performed using the elasto-plastic constitutive law to describe the nonlinear, anisotropic and asymmetric properties of fiber-reinforced composites. As for the yield criterion, the modified Drucker—Prager yield criterion was utilized to represent the anisotropic and asymmetric properties, while the anisotropic hardening was described based on the kinematic hardening with the anisotropic evolution of the back-stress. Experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In the present study, the flow rule Q is considered same as the yield criteria F. In general, hardening rule can be classified as kinematic and isotropic hardening. In order to predict the fatigue effects on composites using theoretical model, few literature studies suggested that the kinematic hardening rule can be used provided cyclic load has minimal effect on its performance [39][40][41]. From this experimental studies, it is identified that the fatigue load has minimal effect on the actuation performance of MFCs before sudden failure (refer figure 4).…”
Section: Materials Nonlinearitymentioning
confidence: 97%
“…In the present study, the flow rule Q is considered same as the yield criteria F. In general, hardening rule can be classified as kinematic and isotropic hardening. In order to predict the fatigue effects on composites using theoretical model, few literature studies suggested that the kinematic hardening rule can be used provided cyclic load has minimal effect on its performance [39][40][41]. From this experimental studies, it is identified that the fatigue load has minimal effect on the actuation performance of MFCs before sudden failure (refer figure 4).…”
Section: Materials Nonlinearitymentioning
confidence: 97%